2018
DOI: 10.5902/1980509831615
|View full text |Cite
|
Sign up to set email alerts
|

AVALIAÇÃO DA QUALIDADE FISIOLÓGICA DE SEMENTES DE <i>Moringa oleifera </i>Lam.

Abstract: RESUMOOs principais testes que avaliam a qualidade de sementes são destrutivos e exigem um tempo relativamente longo para serem concluídos. A análise de imagens de sementes por meio de raios X representa uma alternativa para este setor, sendo uma técnica reproduzível e rápida, permite maior agilidade e autonomia nas atividades dos sistemas de produção. O objetivo deste trabalho foi analisar a morfologia interna de sementes de moringa por meio de imagens radiografadas e compará-la aos testes de germinação e vig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 6 publications
(10 reference statements)
0
19
0
5
Order By: Relevance
“…Application of the X-ray test in seeds of forest species such as Moringa oleifera (Noronha;Pereira, 2018), Senna multijuga (Marchi;Gomes Junior, 2017), and Terminalia argentea (Gomes et al, 2014) also showed a relationship between the internal morphology of the seeds and their physiological quality. However, other parameters of assessment were used to characterize the internal morphology of the seeds, such as identification of full seeds and malformed seeds, damage by insect predation, percentage of empty internal area, and embryo size.…”
Section: Resultsmentioning
confidence: 93%
See 3 more Smart Citations
“…Application of the X-ray test in seeds of forest species such as Moringa oleifera (Noronha;Pereira, 2018), Senna multijuga (Marchi;Gomes Junior, 2017), and Terminalia argentea (Gomes et al, 2014) also showed a relationship between the internal morphology of the seeds and their physiological quality. However, other parameters of assessment were used to characterize the internal morphology of the seeds, such as identification of full seeds and malformed seeds, damage by insect predation, percentage of empty internal area, and embryo size.…”
Section: Resultsmentioning
confidence: 93%
“…The use of parameters such as relative density, integrated density, and descriptive features of shape associated with semi-automated tools, such as ImageJ ® , effectively contributed to reduction in time of assessment of seed quality, as well as totally removed the error inherent to subjectivity of the analyst, which, according to Gomes-Junior (2010), is a current concern of research for the purpose of establishing greater reliability of the results obtained. Studies performed on Moringa oleífera (Noronha;Pereira, 2018) and Acca sellowiana (Silva et al, 2013) showed the potential of the ImageJ ® software in evaluation of radiographs directed to determination of empty and filled areas of the internal cavity of the seed, relating them to seed physiological quality. Prado-Alves et al (2018) also indicated ImageJ ® as a good alternative in aiding identification of differences in physiological potential of seed lots of scarlet eggplant (Solanum gilo) in different stages of maturity.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies have demonstrated the efficiency of X-ray technique for application in various studies with seeds [4][5][6][7]. However, the radiographs analysis may be compromised when radiographic images are evaluated by human visual, since the process is slow and can generate interpretation errors [6].…”
Section: Introductionmentioning
confidence: 99%